Jack Ryan : Clear and present danger - Neufeld, Mace.; Rehme, Robert, 1935-; Stewart, Donald E.; Zaillian, Steven; Milius, John.; Noyce, Phillip; Ford, Harrison, 1942-; Dafoe, Willem; Archer, Anne.; Jones, James Earl.; Almeida, Joaquim de, 1957-; Czerny, Henry; et al. (Hollywood, Calif. : Paramount Pictures, 2003)
CIA Agent Jack Ryan is appointed acting CIA Deputy Director of Intelligence when his mentor, Admiral James Greer becomes gravely ill. His first assignment is to investigate the murder of one of the president's friends, a prominent U.S. businessman with secret ties to Colombian drug cartels. Caught in the crossfire, Ryan takes matters into his own hands.
Based on the novel by Tom Clancy.
Harrison Ford, Willem Dafoe, Anne Archer, James Earl Jones, Joaquim de Almeida, Henry Czerny, Miguel Sandoval, Donald Moffat, Benjamin Bratt.
DVD video; Dolby digital, DTS, 5.1 surround, Region 1 encoding.
Keywords: United States. -- Central Intelligence Agency; Homicide investigation; Drug traffic -- Colombia; Feature films; Thrillers (Motion pictures); Action and adventure films